KAJI EKSPERIMEN MESIN KOMPRESI UDARA DENGAN MEMODIFIKASI GIGI SENTRIS MOTOR BENSIN 4-TAK SEBAGAI SOLUSI ALTERNATIF KENDARAAN BERMOTOR BEBAS EMISI - Darwin Rio Budi Syaka; Triyono; Mohammad Joko Triyanto (Jurnal Konversi Energi dan Manufaktur, 2022)
The compressed air engine is an environmentally friendly alternative with the advantages of zero emissions and a fast-charging process making it suitable for application as the main power source in vehicles. Previous research on compressed air power engines that modify the internal combustion engine was carried out by changing the shape of the camshaft. This is complicated, so another solution is to change the gear-centric ratio. However, research on centric gear modification is still not available. Therefore, this study aims to determine the performance of a compressed air engine with centric gear modification. This research presents an experimental study of a piston engine driven by compressed air where the test equipment is a 4-stroke internal combustion engine which is converted to a 2-stroke by modifying the centric gear ratio from 2:1 to 1:1. The torque produced by the engine is measured using a prony brake where variations in a brake pressure range from 0.4 bar to 2 bar with a change in brake pressure every 0.2. The variations in air pressure between 3 bar - 9 bar with a change in air pressure of 1 bar. The resulting engine speed is measured using a tachometer. The results of this study indicate that air pressure is the main factor affecting the performance of a compressed air engine, the greater the pressure of the compressed air, the greater the power generated. The best performance of the compressed air engine is at the highest air pressure experiment, which is 8 bar by producing 2.36 kW of power at 724.33 rpm engine speed with 31.09 Nm of torque, but the highest torque that can be obtained is 34.55 Nm at 618.67 rpm.